Contribution of Genetics to the Susceptibility to Hidradenitis Suppurativa in a Large, Cross-sectional Dutch Twin Cohort - Kelsey R. van Straalen; Errol P. Prens; Gonneke Willemsen; Dorret I. Boomsma; Hessel H. van der Zee (2020)
Importance Hidradenitis suppurativa is a chronic, inflammatory skin disease in which genetic factors are considered to play a role, with up to 38% of patients reporting a family history. Variations in the γ-secretase genes are found mainly in familial cases with an autosomal dominant pattern of inheritance. These variations are rare in the general population with hidradenitis suppurativa, even in patients who report a family history of the disease. Objective To assess the heritability of hidradenitis suppurativa in a nationwide Dutch twin cohort. Design, Setting, and Participants In this cross-sectional study on self-reported hidradenitis suppurativa conducted from 2011 to 2016, data were collected from twins participating in the surveys of the nationwide Netherlands Twin Register. All complete twin pairs answering the question on hidradenitis suppurativa in the survey were included: 978 female monozygotic twin pairs and 344 male monozygotic twin pairs and 426 female dizygotic twin pairs, 167 male dizygotic twin pairs, and 428 dizygotic twin pairs of the opposite sex. Statistical analysis was performed from July to November 2019. Main Outcomes and Measures The main outcome is the proportion of susceptibility to hidradenitis suppurativa due to additive genetic factors (narrow-sense heritability), dominant genetic factors, common or shared environmental factors, or unshared or unique environmental factors. The main outcome was evaluated prior to data collection. Results The prevalence of hidradenitis suppurativa among twin pairs was 1.2% (58 of 4686); the mean (SD) age was 32.7 (15.4) years. The narrow-sense heritability of hidradenitis suppurativa was 77% (95% CI, 54%-90%), with the remainder of the variance due to unshared or unique environmental factors based on an age-adjusted model combining additive genetic factors and unshared or unique environmental factors. Conclusions and Relevance The high heritability found in this study suggests a stronger than previously assumed genetic basis of hidradenitis suppurativa. Environmental factors were also shown to contribute to the susceptibility to hidradenitis suppurativa, supporting a multifactorial cause of the disease. Moreover, the results of this study strongly support the need for a global genome-wide association study in the general population of patients with hidradenitis suppurativa.